1967
DOI: 10.1126/science.155.3764.841
|View full text |Cite
|
Sign up to set email alerts
|

Direction-Selective Units in Rabbit Retina: Distribution of Preferred Directions

Abstract: The preferred directions of 102 direction-selective ganglion cells in the rabbit retina have been determined. Cells of the "on-off" type form four nonoverlapping groups; cells of the "on" type fall into three groups. The on-off groups appear to correspond to the directions of apparent object displacement produced by contractions of the four rectus muscles. Each group of cells could, without further processing, provide the error signal for a visual servo-systerm minimizing retinal image motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
2
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(148 citation statements)
references
References 7 publications
12
133
2
1
Order By: Relevance
“…2F. It is very obvious that the distribution of LGN DS cell preferred directions (black) forms four groups (anterior, posterior, superior, and inferior), resembling the distribution of ON_OFF DS ganglion cells in the rabbit retina (Oyster and Barlow 1967). In contrast, the preferred directions of cortical simple cells (red) are more homogeneously distributed.…”
Section: D E and F)mentioning
confidence: 90%
See 1 more Smart Citation
“…2F. It is very obvious that the distribution of LGN DS cell preferred directions (black) forms four groups (anterior, posterior, superior, and inferior), resembling the distribution of ON_OFF DS ganglion cells in the rabbit retina (Oyster and Barlow 1967). In contrast, the preferred directions of cortical simple cells (red) are more homogeneously distributed.…”
Section: D E and F)mentioning
confidence: 90%
“…The representation of the visual streak is located roughly midway along the dorso-ventral axis within the rabbit LGN, whereas the upper visual field is represented dorsally (Holcombe and Guillery 1984;Hughes 1971). We examined the visual response properties of LGN DS neurons and showed that their responses are highly nonlinear, that they consist of highly overlapping ON and OFF subfields, and that their preferred directions are, like their counterparts in the retina (Oyster and Barlow 1967), restricted to the four cardinal directions. Notably, each of these visual response properties are dramatically distinct from those of V1 layer 4 simple cells studied in the same preparation using identical methods (Zhuang et al 2013), suggesting that LGN DS neurons do not contribute strongly to the synthesis of the direction/orientation selectivity seen in V1 simple cells.…”
mentioning
confidence: 99%
“…Some types of RGCs respond selectively to the direction of motion (Cronly-Dillon, 1964;Barlow and Levick, 1965;Oyster and Barlow, 1967;Pearlman and Hughes, 1976). In the rabbit retina, direction-selective RGCs account for ϳ10% of all RGCs (Vaney, 1994;Vaney et al, 2001;Taylor and Vaney, 2003).…”
Section: Retinal Direction Selectivitymentioning
confidence: 99%
“…The ON-OFF DS cell class harbors four vector types (Oyster and Barlow, 1967) and lies in the small-to-medium soma size spectrum (Amthor et al, 1989b). Because vector type might display a well patterned distribution (Vaney, 1994b) and a single class contains two or more vector types, that class might show mixed distribution patterns.…”
Section: On-off Ds Cellsmentioning
confidence: 99%
“…In addition, some patterns might represent mixed "subclasses." For example, we know that ON-OFF direction-selective (DS) ganglion cells exist as four vector subclasses (Oyster and Barlow, 1967) but that they are not morphologically distinguishable (Amthor et al, 1989b). Any class that contains the ON-OFF DS cells should be represented by a mixture of patterns (a "mixed" pattern).…”
Section: Structural Correlates Of Classesmentioning
confidence: 99%